Smartboard-Mediated CSCL Scripts to Improve Oral Communication in Eastern Indonesia: A Quasi-Experimental Study - Kaharuddin; Sitti Hajar; Zul Fadhli Al Alim; Andi Kaharuddin; Topanus Tulak; Ganjar Susilo; Devasis Pradhan (Information Technology Education Journal, 2026)
Purpose – This study aims to challenge the "hardware fallacy" by investigating how a structured Computer-Supported Collaborative Learning (CSCL) intervention can mediate smartboard affordances to enhance oral communication skills among junior high school students in Eastern Indonesia, a context characterized by teacher-centered instruction and student speaking anxiety. Design – A quasi-experimental non-equivalent control group design was employed with 64 eighth-grade students from two intact classes (n = 32 each) assigned to conditions; analyses treated students as individuals. The control group (n=32) used smartboards for teacher-centered presentations, while the experimental group (n=32) participated in an eight-week CSCL intervention involving collaborative sorting, visual debate mapping, and interactive presentation tasks. Oral communication performance was assessed using a validated analytic rubric with excellent inter-rater reliability (ICC = .87). Findings – ANCOVA revealed a statistically significant effect of the intervention on post-test communication scores F (1,61) = 109.65, p < .001, partial η² = .642), with the most pronounced gains in communicative confidence (partial η² = .712). Qualitative observations showed 88% of experimental students physically interacting with the smartboard, with a recurrent pattern of non-verbal manipulation preceding verbal justification, indicating cognitive offloading. Research implications – The quasi-experimental design and single-school setting limit generalizability, and the 8-week duration cannot confirm long-term sustainability. However, findings provide empirical evidence for the necessity of pedagogical redesign alongside technology investment to bridge the second-level digital divide. Originality – This study advances CSCL research by specifying mechanisms (shared visual anchoring, embodied offloading) through which smartboard affordances are pedagogically engineered to address cultural barriers in under-resourced Southeast Asian classrooms, offering a replicable intervention model for similar contexts. Replication materials are available in the online supplement.